Phylogenetic relationship between Barbonymus gonionotus, Barbonymus schwanenfeldii, and Tor tambroides inferred from mitochondrial cytochrome c oxidase I (COI) sequence analysis - Siti Rawaida Rozali. (2013)
The study examined the phylogenetic relationships between the Cyprinids fishes Barbonymus gonionotus, Barbonymus schwanenfeldii and Tor tambroides using DNA sequencing of mitochondrial cytochrome c oxide I (COI) gene fragment using polymerase chain reaction. Sequencing of DNA samples were compared to the DNA reference sequence sample in GenBank using the BLAST program. Phylogenetic analysis of eight sequences using maximum likelihood (ML), minimum evolution (ME), and neighbor joining (NJ) resulted in similar tree topologies. The maximum pairwise genetic distance was Barbonymus gonionotus and Tor tambroides (15%), while the minimum value was between Barbonymus gonionotus and Barbonymus schwanenfeldii (11%). Comparative genetics of the genus Tor and Barbonymus not show a significant difference to the value of 16%.